Social bonds provide multiple pathways to reproductive success in wild male chimpanzees - Joseph T. Feldblum; Christopher Krupenye; Joel Bray; Anne E. Pusey; Ian C. Gilby (iScience, 2021)
Summary: In most male mammals, fitness is strongly shaped by competitive access to mates, a non-shareable resource. How, then, did selection favor the evolution of cooperative social bonds? We used behavioral and genetic data on wild chimpanzees (Pan troglodytes schweinfurthii) in Gombe National Park, Tanzania, to study the mechanisms by which male-male social bonds increase reproductive success. Social bonds increased fitness in several ways: first, subordinate males that formed strong bonds with the alpha male had higher siring success. Independently, males with larger networks of strong bonds had higher siring success. In the short term, bonds predicted coalition formation and centrality in the coalition network, suggesting that males benefit from being potential allies to numerous male rivals. In the long term, male ties influenced fitness via improved dominance rank for males that attain alpha status. Together, these results suggest that male bonds evolved in chimpanzees by affording both short- and long-term pathways to reproductive success.